EVALUASI IMPLEMENTASI KEBIJAKAN SISTEM PENYULUHAN PERTANIAN DI KABUPATEN BEKASI - Rasminto Rasminto (Jurnal Ilmiah Pendidikan Lingkungan dan Pembangunan, 2016)
Bekasi regency as one of the mainstays of agriculture of West Java province is one area that can not escape from the problems of human resource development of agriculture that should get attention by local governments, the private sector and local communities. Many factors that cause deterioration of agriculture in Bekasi Regency, among others; not optimal function of the institution / organization of Agricultural Extension, operational techniques ranging from counseling; extension of distribution, identification of potential areas of extension, aspects of planning and implementation. The purpose of this study was to evaluate the implementation of agricultural extension in Bekasi based aspects of the functions of institutions / organizations and operational technical extension further identify potential areas of agricultural extension.The method used in this study is a qualitative method, ie by observation, interviews and observations documents.The results showed that: (1) Institutions / organizations that form the Executive Agency of Agricultural Extension as an institution is still limited motion in terms of both quantity and quality of personnel, bergaining institutions still sometimes overlaps with the Department of Agriculture. (2) There are still required the addition and improvement of facilities / infrastructure of agricultural extension services so as to improve the quantity and quality of the target areas. (3) Implementation of outreach are still many obstacles execution as their major influence on the political Pilkades, information outreach activities that still have not been absorbed by the farmer that still few farmers who take part in counseling, technology transfer and transfer of regeneration as a target of the main actors, and the synergy between the authorities village extension workers are not optimal.